Ketersediaan dan Pemanfaatan Ruang Sosial di SDN 179 Kecamatan Kemuning Kota Palembang - Depy Amelia; Ridhah Taqwa; Diana Dewi Sartika (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2016)
Issues raised is how the availability and utilization of school facilities as an arena of social space and the types of activities that can form a social space. This study was a descriptive qualitative study. The results showed that school facilities are available at SDN 179 include adequate and can support the activities of both students and teachers at school. Availability of school facilities as an arena of social space that includes a field school, 'canteen honest', and the mosque which became the arena of social space for students to interact, play and set up in cooperation with the other students. In addition to school facilities, types of activities in this school can also shape the social space. This school has two types of activities, namely academic activities such as learning and courses, as well as extracurricular activities that include Scouts, Sports, Drum Band and Karate. However, activities that can form a social space is Scout activities and sports in which this activity is the most widely followed by students. In the lead this activity, students can mingle and interact directly with other students and teachers. Students make this activity as a social space as a place to establish interaction, cooperation and familiarity with other students.